Feline Infectious Peritonitis, Two Different Manifestations of the Effusive Form. Case Report - Ševčíková Zuzana; Márková Katarína; Mandelík René; Zákutná Ľubica; Hudec Erik; Karaffová Viera (Folia Veterinaria)
Feline infectious peritonitis (FIP) is a systemic, potentially fatal viral disease of domestic and wild felids. This study demonstrates the pleural and abdominal manifestation of the effusive form of FIP from the clinical and pathological points of view. Two approximately one-year-old cats (male and female) are presented. A set of clinical (haematology, biochemistry), morphological (cytology, necropsy histopathology and immunohistochemistry) and other diagnostic assays (PCR, FIP antibodies detection, protein electrophoresis) were carried out. The results, like lymphopenia, lower A/G ratio, and hyperbilirubinemia are among the most characteristic signs for FIP. The morphology revealed the occurrence of effusions, severe diffuse adhesive pleuritis, icterus, vasculitis/perivasculitis, severe liver and lungs alteration and granulomatous-like reactions with the presence of giant cell type macrophages in the lungs. At the end of this work a list of tests required for FIP diagnosis is mentioned.